The role of electronic news websites in enhancing national identity among university students at the University of Jordan (2011-2015) - Abu Rumman, Hamza Khalaf (Journal of Humanities & Social Sciences, 2024)
This study aimed to clarify the concept of electronic news websites and Jordanian national identity, and to analyze the impact of electronic news websites on enhancing Jordanian national identity among students at the Prince Hussein College for International Studies. The study employed integrated methodologies: descriptive and analytical. The descriptive approach was used to provide a comprehensive theoretical framework on electronic websites and Jordanian national identity, while the analytical approach was adopted in the field aspect of the study through a specially designed questionnaire for data collection and analysis. The study included a random sample of 200 students from the Prince Hussein College for International Studies, who were distributed questionnaires. The results indicated that Arabic TV series were the most watched programs at 32.5%, followed by game shows at 27%. Foreign films, Arabic and foreign music programs were perceived as less important compared to other types of programs. Additionally, the study showed a positive impact of electronic news websites on Jordanian national identity, with an overall mean of 3.45, exceeding the assumed mean of 3. Among the items, statement number 15 had the highest positive impact mean at 4.04, whereas statement number 3 had the lowest impact with an average response of 2.88, below the assumed mean of 3. Based on these results, the study recommends that the Jordanian media adopts a national strategy that enhances loyalty and belonging among Jordanian citizens through cultural and political programs aimed at strengthening national identity, focusing on students and youth who are more exposed to electronic news websites and their impact on their national identity. The study also advises enhancing cooperation between local media institutions such as Jordanian television, radio, newspapers, educational and educational institutions, to develop a comprehensive national plan to deal with foreign media and raise awareness among Jordanian society about the dangers of some programs on these media, especially targeting youth and students.
Keywords: Electronic news websites; Jordanian national identity; University of Jordan students